PEMENUHAN HAK DAN TANGGUNG JAWAB KONSUMEN DAN PELAKU USAHA SEBAGAI UPAYA PERLINDUNGAN HUKUM MELALUI KONSEP PEMBERDAYAAN: (Studi Di Kawasan Wisata Pantai Gemah Tulungagung) (Ahkam: Jurnal Hukum Islam, 2020)
Often the losses experienced by consumers in conducting transactions are the result of ignoring the responsibilities of business actors as stipulated in the Consumer Protection Law Number 8 of 1999 concerning Consumer Protection. The losses also happen because consumers often do not have the courage to defend their rights due to the lack of courage and helplessness due to a one-sided take-or-leave-it contract that gives business actors more authority so that the two parties are not in a balanced and equal position. Therefore, empowering consumers by showing their rights and how to defend their rights is important. Likewise, with the empowerment of business actors which emphasizes the fulfillment of their responsibilities, it is possible that the products and / or services offered have a small possibility of detrimental to consumers. In return, it also benefits to business actors in increasing the level of marketing of their products. Keywords: Empowerment, Consumers, Bussines Actors, Fulfillment or Rights and Responsibilities.
Keywords: Empowerment, Consumers, Bussines Actors, Fulfillment or Rights and Responsibilities.